Fatwa Tentang Kebakaran Hutan Dan Lahan Serta Pengendaliannya Dalam Perspektif Hukum Islam Dan Negara - Yahya Muhajir Fadholi; Mutya Octarisa Nur Andini; Ali Asad (Isti`dal : Jurnal Studi Hukum Islam, 2023)
Forests are an integral part of the life of the people who surround them. Living natural resources. Forests and land as gifts from Allah Swt are important to be maintained, preserved and used for the common good. Efforts to use community land and forests are often driven by burning, causing damage and loss. Forest and land fires are caused by 2 (two) general factors, namely natural factors and uncontrolled human activities. This study uses the understanding study method, namely data collection by searching books, magazines and online articles. The author seeks and collects data which is then collected and analyzed. The legal implication in the study of fiqh studies, ihya' al-mawat is that obtaining ownership rights to land is sought by ihya' al-mawat and applies to all types of land. However, in Indonesian law, land law is different from the reality, that is, there are separate rules for land management. During the dry season, especially during the extreme dry season because currently forest/land fires in Indonesia actually have several laws and regulations that are quite good at preventing forest and land fires for decades. However, all laws and regulations seem powerless to prevent karhutla from happening. Supervision and prosecution have proven to be a burden on the government and difficult to achieve optimally.